Social Education: paths covered , challenges and contemporary opportunities. Approaches between Portugal and Brazil - Sílvia Azevedo; Fátima Correia; Érico Ribas Machado; Jacyara Silva de Paiva (Escola Superior de Educação de Paula Frassinetti, 2017)
This article intends to be a contribute to legitimize the paths covered, challenges and contemporary opportunities that approach the affirmation of Social Education as a professional authority in Portugal and Brazil. It presents the history of forthcoming socioeducative processes, the affirmation of the profession, the importance of professional associations and the future challenges of professionalization in both countries.